2019
DOI: 10.7717/peerj.6797
|View full text |Cite
|
Sign up to set email alerts
|

Fish nursery value of algae habitats in temperate coastal reefs

Abstract: The nursery function of coastal habitats is one of the most frequently mentioned and recognized ecosystem services in the valuation of coastal ecosystems. Despite its importance our understanding of the precise habitat parameters and mechanisms that make a habitat important as a nursery area is still limited for many species. The study aimed to establish the importance of different algae morphotypes in providing shelter and food for juvenile coastal fish during the main settlement peaks, in early spring and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Habitat and seascape tri-dimensional structure can be qualified by its heterogeneity and complexity 90 , 91 . Generally high quality habitats for juvenile fishes are recognized to be associated with high degrees of three-dimensional structuration 92 , in terms of both complexity 51 , 53 , 93 , 94 and/or heterogeneity 42 . Natural rocky habitats (RS) presented a high structural and biological complexity due to different macrophytes assemblages, and indeed supported the highest mean species richness and abundance of juvenile fishes in the two sampling period (cold and warm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Habitat and seascape tri-dimensional structure can be qualified by its heterogeneity and complexity 90 , 91 . Generally high quality habitats for juvenile fishes are recognized to be associated with high degrees of three-dimensional structuration 92 , in terms of both complexity 51 , 53 , 93 , 94 and/or heterogeneity 42 . Natural rocky habitats (RS) presented a high structural and biological complexity due to different macrophytes assemblages, and indeed supported the highest mean species richness and abundance of juvenile fishes in the two sampling period (cold and warm).…”
Section: Discussionmentioning
confidence: 99%
“…However, the higher abundance of juveniles in seagrass bed habitats and rocky substrates during the warm period could be related to the greater protection and food resources provided by the greater canopy height of Posidonia oceanica and macroalgae communities 50 , 51 , 53 . The role of highly complex Cystoseira forest canopies with regard to the composition of juvenile fish assemblage was well studied by Cheminée et al 50 , 51 , Cuadros et al 52 and Hinz et al 53 , who demonstrated that Symphodus spp., Labrus spp. and Serranus spp.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to mention the small, resident species that also have ecological significance in the benthic communities of transitional waters, e.g., Salaria pavo, S. ocellatus, and Z. ophiocephalus, as these herbivorous and omnivorous fishes seem to control both algae and invertebrates in rocky sub-littoral zones (Ruitton et al, 2000). S. ocellatus showed a significant association with an algal habitat, and its abundance can certainly be related to the strong seasonal differences in algal cover (Hinz et al, 2019). If species preferring transitional waters at higher latitudes also spawn in winter and/or early spring, such as D. vulgaris, D. sargus, S. aurata and D. labrax, this makes them particularly sensitive to interannual differences in environmental conditions.…”
Section: More Sensitive Speciesmentioning
confidence: 99%
“…Coastal areas are commonly acknowledged as highly productive and valuable ecosystems that provide many favourable habitats for fish, while also supporting fundamental ecological links with other environments (Duarte, 2000;Beck et al, 2001;Hinz et al, 2019). Their role in early life stages, and also as foraging and spawning grounds for non-coastal fish species (Harmelin-Vivien, 1984;Francour et al, 1999) is recognised throughout the Mediterranean and worldwide (Francour, 1997;Deudero et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It could be interesting to integrate algal cover, which can be a proxy of complexity (Cuadros et al, 2019), such as the cover of Cystoseira sensu lato, in order to simultaneously consider the complexity of the inert substrate but also the complexity built by species such as in macrophytes forests or biogenic reefs, as well as with the depth factor. In addition, it is known that many fishes graze on epilithic algae (Gratwicke and Speight, 2005;Hinz et al, 2019), and that Cystoseira may provide preferred habitats for coastal fishes throughout their life stages (Lejeune, 1987;Rodrigues, 2010;Cheminée et al, 2013;Thiriet et al, 2014Thiriet et al, , 2016Thibaut et al, 2017;Hinz et al, 2019).…”
Section: Teleost Assemblagesmentioning
confidence: 99%